Fine structural evidence for hormone secretion by the human thymus - Vetters, J. M. (1973)
The epithelial cells of the Hassall's corpuscles in 11 human thymus glands (nine cases of myasthenia gravis and two glands from patients undergoing surgical correction of congenital heart disease) have been examined by electron microscopy. In every instance the epithelial cells have the cytoplasmic organelle complex necessary for `export'-type secretory activity and in addition contain large numbers of membrane-limited small spheroidal secretion granules. Hassall's corpuscles are avascular anatomical units and a pericorpuscular zone, at least 50 μm broad, is also without blood vessels. It is therefore suggested that the secretory product(s) of the corpuscular epithelial cells has a purely intrathymic function.